Dendritic cell therapy in melanoma - Alvarez-Dominguez, Carmen (Ann Transl Med, 2017)
Dendritic cell (DC) vaccines are cancer vaccines used currently as melanoma therapies. They act as adjuvants initiating the immune responses, but not only as they can also have effector activities redirecting cytotoxic CD8(+) T cells against melanoma. Ex vivo preparation of monocyte derived DCs has been implemented to produce large numbers of DCs for clinical therapy, highlighting the necessity of activate DC s to produce Th1 cytokines, especially TNF-a and IL-12 with potent anti-tumour actions. Several clinical trials both in the European Union and USA are open currently using DC vaccines, alone or in combination with other immunotherapies. The type of antigen is also an active area of investigation involving tumour antigens and bacterial epitopes, both providing good responses. Bacterial epitopes presented the advantage versus tumour antigens that they can prepare the vaccination site as they induce innate and specific immune responses as they are potent recall antigens that expand cytotoxic responses.